2012
DOI: 10.1371/journal.pone.0050348
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Transgene Integration by Next-Generation Sequencing in Transgenic Cattle

Abstract: As the number of transgenic livestock increases, reliable detection and molecular characterization of transgene integration sites and copy number are crucial not only for interpreting the relationship between the integration site and the specific phenotype but also for commercial and economic demands. However, the ability of conventional PCR techniques to detect incomplete and multiple integration events is limited, making it technically challenging to characterize transgenes. Next-generation sequencing has en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…The multiple or incomplete integration events pose technical challenges for characterization of transgenes using PCR-based chromosome-walking techniques (Tonooka et al 2009;Zhang et al 2012). In this study, we were confronted with a severe challenge for conventional PCR amplification due to the poly G region of the ubiquitin promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple or incomplete integration events pose technical challenges for characterization of transgenes using PCR-based chromosome-walking techniques (Tonooka et al 2009;Zhang et al 2012). In this study, we were confronted with a severe challenge for conventional PCR amplification due to the poly G region of the ubiquitin promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports demonstrated that integration sites influence transgene expression levels (Grosveld et al, 1987;Williams et al, 2008), while in some case, integration positions have no effect on transgene expression (Wang et al, 2010). However, the inserted DNA may cause rearrangement of endogenous genes (Le Saux et al, 2010;Zhang et al, 2012) and result in genome variation. Several PCR-based methods have been described to precisely determine the integration site of exogenous DNA into native chromosomes, including inverse PCR , ligation-mediated PCR (Yuanxin et al, 2003), and TAIL-PCR (Yan et al, 2010(Yan et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic cell nuclear transfer (SCNT) is a conventional method for gene transfer into livestock, in which foreign DNA fragments often randomly integrate into the genome of donor cell, resulting in tandem repeats encompassing several copies of exogenous genes. Additionally, random integration of exogenous gene can often cause deletions or rearrangements in the genome (Le Provost et al, 2010;Zhang et al, 2012). When new transgenic animals are produced, an essential step is to determine the copy number and insertion sites of the inserted genes in the transgenic animals.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the recent studies, the authors successfully demonstrated the utilization of next-generation sequencing technology to characterize cattle harboring a 150 kb Bacterial artificial chromosome (BAC) that expresses human lactoferrin [1]. The author's initial attempt to characterize it with the conventional chromosome walking was met with no success [1].…”
mentioning
confidence: 99%
“…The author's initial attempt to characterize it with the conventional chromosome walking was met with no success [1].…”
mentioning
confidence: 99%